ANALYSIS OF CORPORATE CULTURAL VALUE ON THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT PT BANK SULSEL - AM Fadly Mappisabbi (Center for Study and Journal Management FTI UMI, 2022)
This study aims to determine the effect of corporate culture values (which include: integrity, professionalism, customer focus, and service improvement) on the implementation of good corporate governance at PT. Bank Sul-Sel, as well as knowing which value is more dominant in influencing the good corporate governance of PT. South Sulawesi Bank.The population of this research is 130 employees. The number of samples used the Isaac and Michel formula with an error rate of 5% was set at 77 employees. The data used are primary data and secondary data. Data collection used questionnaires and documentation techniques. The data were analyzed using multiple regression analysis, validity, reliability, and hypothesis testing analysis.The results of the study based on the results of multiple regression analysis indicate that the values of corporate culture, namely: integrity, professionalism, customer focus, and service improvement, positively influence employee performance. The analysis results show that the dominant value that affects employee performance is integrity. It can be seen from the regression analysis results, which shows that t-count = 3.713. The contribution of corporate culture values to good corporate governance is 53.9%. The remaining 46.1% is influenced by other variables not examined.